PERANCANGAN MEDIA PROMOSI PANTAI HUNIMUA UNTUK MENINGKATKAN BRAND AWARENESS - Tesno, Edwin Indra; Fianto, Achmad Yanu Alif; Riqqoh, Abdullah Khoir (Jurnal Art Nouveau, 2014)
The Culture and beach tourism in indonesian, is very desirable to indonesian people and turis, beach tourism in indonesian from sabang to merauke, are beach that has unique traits which are different from the other beach in indonesian. To show the characteristic of the coast and can differentiate with other beaches in Indonesian as Hunimua Beach , Hunimua Beach is one of the beaches that are located in eastern Indonesian Ambon of  Malucas level mask , Hunimua Beach has something unique , different beaches in Indonesian which has white sand 1km and 300m wide and can see dolphins , whales , and sea birds Hunimua Beach , with the Hunimua Beach has beautiful scenery and not be could forget the memory of every visitor who visit the beach Hunimua . With the media promotion to promote Hunimua Coast to Indonesian, Foreign Affairs and especially in Eastern Indonesian , in the presence of the media promotion can improve and attract consumers even higher, and the people of Indonesian and abroad can know Hunimua Beaches , which requires a media in which contains the characteristic of the coast and provide a brand to consumers in order to establish a brand identity that is able to give a special image for the consumer who then embedded in the minds of consumers . The purpose of this design is how to design a media promotion to increase Hunimua Beach Brand Awarenes.